Me-- Jane - McDonnell, Patrick, 1956- (New York : Little, Brown, 2011)
Holding her stuffed toy chimpanzee, young Jane Goodall observes nature, reads Tarzan books, and dreams of living in Africa and helping animals. Includes biographical information on the prominent zoologist.
Parents' Choice, January 2011
Wilson's Children, September 2011
School Library Journal, April 2011
Booklist starred, March 2011
Horn Book Starred, March 2011
Publisher's Weekly, February 2011
Keywords: Goodall, Jane, -- 1934- -- Childhood and youth -- Juvenile fiction; Nature study -- Juvenile fiction; Toys -- Juvenile fiction; Goodall, Jane, -- 1934- -- Fiction; Nature study -- Fiction; Toys -- Fiction; Goodall, Jane, -- 1934- -- Fiction; Nature study -- Fiction; Toys -- Fiction; Picture books for children